Breaking down barriers to mental healthcare access in prison: a qualitative interview study with incarcerated males in Norway - Line Elisabeth Solbakken; Svein Bergvik; Rolf Wynn (BMC Psychiatry, 2024)
Abstract Background Mental health problems are highly prevalent in prison populations. Incarcerated persons generally come from disadvantaged backgrounds and are living under extraordinary conditions while in prison. Their healthcare needs are complex compared to the general population. Studies have found that incarcerated individuals are reluctant to seek help and that they experience challenges in accessing mental healthcare services. To some extent, seeking treatment depends on the degree of fit between potential users and health services, and actual use might be a better indication of accessibility than the fact that services are available. This study aimed to explore individual and systemic facilitators and barriers to accessing mental healthcare in a prison context. Methods An analytical approach drawing on elements of constructivist Grounded theory was the methodological basis of this study. Fifteen male participants were recruited from three prisons in Northern Norway. Data was collected through in-depth interviews on topics such as help-seeking experiences, perceived access to services and availability of health information. Results We found that distrust in the system, challenges with the referral routines, worries about negative consequences, and perceived limited access to mental healthcare were barriers to help-seeking among incarcerated individuals. How prison officers, and healthcare personnel respond to incarcerated persons reporting mental distress could also be critical for their future willingness to seek help. Providing information about mental health and available services, initiating outreaching mental health services, and integrating mental health interventions into treatment programs are examples of efforts that might reduce barriers to accessing services. Conclusions Facilitating access to mental health services is crucial to accommodate the mental health needs of those incarcerated. This study provides insights into the complex interplay of individual, social and systemic factors that may contribute to the utilization of mental health care among incarcerated persons. We suggest that correctional and healthcare systems review their practices to facilitate access to healthcare for people in prison.